A REAL STRETCH : AN Elastigirl PREQUEL STORY - Jablonski, Carla (Los Angeles : Autumn Publishing, 2018)
Elastigirl works to protect the people of Municiberg using her stretchy powers as she tries to find a better mode of transportation, attends a Super event she does not agree with, and meets an arrogant Super named Mr. Incredible.
At head of title: Disney Pixar Incredibles 2.
Keywords: Superheroes -- Juvenile fiction